Experimental Study on the Comprehensive Identification and Improvement of Dispersive Soil in Western Jilin Province, China. (15th September 2021) - Yang, Jun; Song, Yi; Fu, Rui; Lu, Changwei; Liu, Hongcheng
Abstract : In this study, physical experiments, clay mineral determination, and pH testing were performed to examine the basic properties of soil samples from a soil material yard selected for dam construction at Hua'ao Lake, Qian'an County, Jilin Province, China. The results show that the soil in the study area is cohesive, the mineral content of illite in the illite/montmorillonite mixed layer is approximately 50%, and the pH value of the environment from which the soil samples were taken is 8.43-8.91. These factors enable the soil in this area to be dispersed. The dispersibility of the soil sampled from this area was evaluated by a double hydrometer test, a pinhole test, a fragmentation test, a sodium adsorption ratio test, and determination of the percentage of exchangeable sodium ions. Because these test methods had inconsistent results, the test methods in combination with the typical geomorphic conditions of the sampling points were ultimately used to comprehensively evaluate the soil dispersion. The results demonstrate that the cohesive soil sampled from the soil material yard is dispersible and must be treated with improvement measures before it can be used as a filling material for the dam. To improve the dispersive and transitional soil, 2%, 3%, 4%, 5%, and 6% L1 Fa2 (a 1 : 2 ratio of lime and fly ash) and C1 L1 Fa4 (a 1 : 1 : 4 ratio of cement, lime, and fly ash) were used to perform improvement tests on 10 groups of dispersive soil samples and 10 groups of transitional soil samples. The results reveal that the addition of 4% L1 Fa2 best improves the dispersive soil in this area. Therefore, the soil intended for this project should be used as a dam-building material after improvement with the 4% addition of L1 Fa2 .